2011
DOI: 10.1007/s00125-011-2198-1
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic retinopathy in type 1 diabetes—a contemporary analysis of 8,784 patients

Abstract: Aims/hypothesis The aim of this study was to analyse the risk profile for diabetic retinopathy under real-life conditions in a large cohort of patients with type 1 diabetes. Methods Patients (n=18,891) with childhood, adolescent or adult onset of type 1 diabetes from the prospective German Diabetes Documentation System survey were analysed. A total of 8,784 patients fulfilled the inclusion criterion, which was availability of retinopathy status. Retinopathy grading (any retinopathy, advanced retinopathy), trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
88
4
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 49 publications
(38 reference statements)
14
88
4
9
Order By: Relevance
“…In concert with the current study no association has been found between the incidence or progression of diabetic retinopathy and smoking in cross-sectional and cohort studies [16,17]. However, the association of smoking with diabetic retinopathy found in two cohort studies does reveal a discrepancy, which might in part be due to different proportion of smokers in various studies [7,18]. Smoking is known to exert a detrimental effect on macrovascular disease and it increases the risk of early death and the microvascular complications of diabetes [25,26].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In concert with the current study no association has been found between the incidence or progression of diabetic retinopathy and smoking in cross-sectional and cohort studies [16,17]. However, the association of smoking with diabetic retinopathy found in two cohort studies does reveal a discrepancy, which might in part be due to different proportion of smokers in various studies [7,18]. Smoking is known to exert a detrimental effect on macrovascular disease and it increases the risk of early death and the microvascular complications of diabetes [25,26].…”
Section: Discussionsupporting
confidence: 50%
“…In their cohort study, smoking status or pack-years were not associated with the incidence or progression of diabetic retinopathy or progression of proliferative retinopathy [17]. However, a significant association between diabetic retinopathy and smoking has been detected in German cohort studies (OR 1.3, 95% CI 1.13-1.48, p=0.0002 in a study by Hammes for any retinopathy and OR 1.44, 95% CI 1.10-1.88, p=0.0075 in study by Muhlhauser for retinopathy and pack years) [18,19] and in DCCT study (R= 0.09, P <0 .001) [7]. Furthermore, in the UKPDS study, the incidence and development of diabetic retinopathy were associated with non-smoking status (OR 0.63, 95% CI 0.48-0.82) [20].…”
Section: Physical Activitymentioning
confidence: 95%
“…This confirms earlier reports of associations between increasing age of onset of T1DM and development and progression of DR (Hammes et al. 2011; Hietala et al. 2013a; Forga et al.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,10 All patients who had at least one visit in 2009 were included. Sociodemographic data including the district of residence, laboratory measures, and clinical data are documented longitudinally.…”
Section: Methodsmentioning
confidence: 99%